THE USE OF SQ3R ON STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION WITH THEIR LEARNING STYLE AT LP3I POLYTECHNIC - Rani Ligar Fitriani; Siti Komala (Wiralodra English Journal, 2024)
This study is prompted by the reality that students' success rate in understanding the reading remains low, necessitating innovation in teaching strategies. The main objective of this study is to evaluate the impact of implementing the SQ3R method on students' reading comprehension. The study aims to analyze students' responses to the SQ3R technique, particularly in the context of their visual learning styles, and to explore students' participation in reading comprehension activities during the use of the SQ3R method. The study design is categorized as a pre-experimental study since it uses a one-group pre-test and post-test. The population under study comprises first-semester students in the Management Informatics program at LP3I Polytechnic, with a total of 33 individuals sampled through random sampling methods. Research instruments include test forms, questionnaires, and observations. Data analysis employs descriptive and inferential techniques. The findings reveal a significant improvement in the students' reading understanding scores from the pre-test (average 65.45) to the post-test (average77.87). Hypothesis analysis confirms that the computed t-value exceeds the critical t-value (8.37 > 2.03), indicating a positive impact of the SQ3R technique intervention on students' reading understanding. The study concludes that the SQ3R approach remarkably enhances students' reading understanding.